الآحاديث الواردة في كتاب "التذكرة" للإمام القرطبي : دراسة نقدية لمائة حديث من الأحاديث غير المخرجة في الكتب الستة - Lilly Suzana binti Shamsu (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
“Al-Tadhkirah” of Imam al-Qurtubi is of great benefit, and it is widely used by the scholars and the general public. However, it does contain some weak and fabricated ahadith. Therefore, this research aims to examine the ahadith and determine their status. The ahadith studied are limited to one hundred from amongst those directly attributed to the Prophet (marfu') and not found in the six canonical Hadith collections. Thus the research started by collecting ahadith of this nature and examining their chains of narration. Then, the critical approach was used to enable us to know the status the prophetic sayings based on existing views of the modern and ancient scholars in this regard, or on personal judgment where no previous research has given any explanation for their status. The study discovered that Imam al-Qurtubi paid attention to preaching to a great extent, however, he was criticized for not consistently selecting authentic prophetic sayings. Furthermore, his approach was characterized by some other inconsistency, as he sometimes mentioned the sanad completely, or incompletely, and he occasionally never relates the prophetic saying to its mukhrij. The research also discovered that of the one hundred ahadith examined most are weak. However, some can be regarded as acceptable due to the fact that they are backed up by other authentic or acceptable ahadith.